Racial Minorities and Affirmative Action/Employment Equity Législation in Canada - Jain, Harish (Relations industrielles / Industrial Relations, 1989)
The purpose of this article is to highlight the disadvantaged status of visible minorities in public and private sector organizations and the need for affirmative action/employment equity programs to ameliorate their disadvantaged statut, to describe and analyze public policy on employment equity at the federal and provincial levels, to evaluate the effectiveness of the federal EE initiatives; and to provide policy implications and recommendations for strengthening public policy initiatives.